2014
DOI: 10.1175/jcli-d-13-00760.1
|View full text |Cite
|
Sign up to set email alerts
|

Intraseasonal Variability in Coupled GCMs: The Roles of Ocean Feedbacks and Model Physics

Abstract: The interaction of ocean coupling and model physics in the simulation of the intraseasonal oscillation (ISO) is explored with three general circulation models: the Community Atmospheric Model, versions 3 and 4 (CAM3 and CAM4), and the superparameterized CAM3 (SPCAM3). Each is integrated coupled to an ocean model, and as an atmosphere-only model using sea surface temperatures (SSTs) from the coupled SPCAM3, which simulates a realistic ISO. For each model, the ISO is best simulated with coupling. For each SST bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
101
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(109 citation statements)
references
References 94 publications
8
101
0
Order By: Relevance
“…This work builds from previous observational and modeling work (i.e., Maloney andEsbensen 2005 and2007;Back and Bretherton 2005;Araligidad and Maloney 2008;Maloney 2009;DeMott et al 2014) that has suggested the importance of wind-induced fluxes for destabilizing the MJO, and supports a recent body of work referred to as moisture mode theory (e.g., Fuchs 2007, 2009;Sugiyama 2009a, b;Sobel et al 2010;Sobel and Maloney 2012).…”
Section: Introductionsupporting
confidence: 77%
“…This work builds from previous observational and modeling work (i.e., Maloney andEsbensen 2005 and2007;Back and Bretherton 2005;Araligidad and Maloney 2008;Maloney 2009;DeMott et al 2014) that has suggested the importance of wind-induced fluxes for destabilizing the MJO, and supports a recent body of work referred to as moisture mode theory (e.g., Fuchs 2007, 2009;Sugiyama 2009a, b;Sobel et al 2010;Sobel and Maloney 2012).…”
Section: Introductionsupporting
confidence: 77%
“…14a, c). Although weak negative moisture anomalies still present in the troposphere, column-integrated moisture tendencies are all positive over the MC and western Pacific, which apparently favor Indian Ocean MJO convection moving over the MC and entering western Pacific (e.g., DeMott et al 2014;Feng et al 2015). On the other hand, western Pacific troposphere for type-II MJO is still very dry with negative column-integrated moisture tendency (Fig.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 94%
“…14d-f) are positive over the MC and western Pacific in all three cases likely due to the evaporation of cloud liquid water (Yanai et al 1973;DeMott et al 2014) and the detrainments of cloud water from shallow cumulus and congestus (Johnson et al 1999). Around 100°E and 120°E (Fig.…”
Section: Vertical Moisture Structures Near the Maritime Continentmentioning
confidence: 89%
See 1 more Smart Citation
“…Although the exact reason is not clear, it is generally believed that inadequate representation and description of moisture processes and the associated scale interactions are likely the major culprit (Fu et al 2006;Sooraj and Seo 2013;Demott et al 2014). Some recent studies have suggested that interactions between different cloud regimes, circulation, and diabatic heating in the boundary layer may play a critical role for the evolution of the BSISO (Chattopadhyay et al 2009;Jiang et al 2011;Abhik et al 2013).…”
Section: Introductionmentioning
confidence: 99%